Work-family conflict and social support: a study of female secretaries in Malaysia - Ahmad, Aminah (Universiti Putra Malaysia Press, 1997)
As more married women participate in the labour force and occupy both work and family roles simultaneously, they tend to experience conflict between work and family roles. This study examined the intensity of work-family conflict experienced by female secretaries in the state of Selangor, Malaysia. The study also analysed the social support that the secretaries received at the workplace from supervisors and co-workers and outside their workplace from husbands, and friends and relatives. Data were gathered through self administered questionnaires from 120 secretaries. The secretaries in this study experienced work-family conflict with varying intensities as they try to fulfill the conflicting demands of work and family roles. They received the least social support from their supervisors, and the most from their husbands. Implications of these findings for married working women in terms of facilities, support services and social support are discussed.